Factors affecting the entrepreneurial spirit: some evidences from rural women of Iran - Mehdi, Nooripoor (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis (UniMAP), 2019)
Link to publisher's homepage at http://ijbt.unimap.edu.my